Exploring Spatial Data Sharing Factors and Strategies for Catchment Management Authorities in Australia - Paudyal, Dev Raj; Mcdougall, Kevin; Apan, Armando (Journal on Geoinformatics, Nepal, 2016)
Spatial information plays a significant role in addressing many decision making process including the catchment decisions. Spatial data sharing is recognized as one of the important components in spatial data infrastructure design and development. This research develops spatial data sharing strategies for the implementation of improved spatial data sharing arrangements between catchment management authorities (CMAs) and state government organizations in Australia. A mixed method research approach was utilized to collect both quantitative and qualitative data from 56 CMAs and the embedded design framework was used for the synthesis and interpretation of the results. The national survey data and case study data were collected and analyzed sequentially using the mixed method design framework. Within, the case study, social network analysis was introduced for analyzing data sharing and provides a new perspective on assessing spatial data sharing relationship. The supplemental case study analysis embedded within a larger national survey provided a supportive role and enhanced the findings from the national survey. The key factors which influence spatial data sharing between state government organizations and CMAs were identified and classified into six major classes as governance, economic, policy, legal, cultural and technical. The nontechnical factors (governance, policy, economic, legal and cultural) were found to be more significant in comparison with the technical factor. Based on these findings, fourteen data sharing strategies were developed. The study suggests that the adoption and implementation of these strategies can assist in overcoming the spatial data sharing issues and hence will contribute to improved spatial data sharing arrangements between regional CMAs and state government organizations in Australia.